Penerapan Pembelajaran Inklusi Pada Materi Menyimak Pesan Lisan Kelas VI SDN Balaraja 03: Pendidikan Inklusi - Hetty Marliani; Enggar Utari (CV. Global Cendekia Inti, 2026)
The implementation of inclusive education in elementary schools is crucial for accommodating student diversity; however, students with intellectual disabilities often face significant cognitive barriers in listening comprehension of oral messages. This study aims to analyze the application and effectiveness of inclusive learning in the material of listening to oral messages for regular students and students with intellectual disabilities in Grade VI of elementary school. The research method used is descriptive qualitative, involving class teachers, regular students, and students with intellectual disabilities as research subjects. Data were collected through participant observation, in-depth interviews, and documentation, which were then analyzed using an interactive model comprising data reduction, data display, and conclusion drawing. The research results indicate that the integration of differentiation strategies, the Universal Design for Learning (UDL) framework, and the Assessment for Learning (AfL) approach can improve the understanding of oral messages in both groups of students. Content modification through simplified language, process adjustment with instruction repetition techniques, and the use of audio-visual-based multimodal media proved effective in overcoming the attention and short-term memory barriers of students with intellectual disabilities. In conclusion, adaptive inclusive learning successfully creates equitable access to learning without neglecting the academic progress of regular students.